The Effects of Initial Laser Intensity on the Nonlinear Optical Properties of The Laser Dye DQOCI Doped Films Using Z-Scan Technique - Jaffar, Amal F. (Iraqi Journal of Science, 2020)
This study is dedicated to investigate the effects of initial laser intensity on the nonlinear optical properties of the laser dye DQOCI dissolved in methanol with a concentration of 10 -5 M and doped with PMMA film. The properties were studied by using open and closed aperture Z-scan technique, with different levels of initial intensity (I0), excited by continuous diode solid-state laser at a wavelength of 532 nm. Three lenses of different focal lengths were employed to change the radius of the Gaussian laser beam and then change the initial intensity. For I0= 6.83 and 27.304 kWatt/cm2, the Z-scan curves show a saturation of absorption (SA) known as the negative type of nonlinearity, in which the absorption coefficient Î² 2 decreases and the transmittance increases with increasing the initial laser intensity. With I0 equal to 3.03 KWatt/cm2, the nonlinear absorption changes from SA to RSA, where the transmittances is reduced with the increase of intensity (zï€½0) as analyzed by the theory of free carrier nonlinearities. The closed aperture z-scan shows a pre-focal transmittance minimum (valley) and a post focal transmittance maximum (peak) which reflects the z-scan signature of a positive nonlinearity (self-focusing) due to Kerr effect. Each of nonlinear refractive index (n2), nonlinear absorption coefficient (Î² 2), and third-order nonlinear optical susceptibility (Ï‡3) are intensity-dependent.